2011
DOI: 10.1371/journal.pone.0018176
|View full text |Cite
|
Sign up to set email alerts
|

Viral Etiologies of Acute Respiratory Infections among Hospitalized Vietnamese Children in Ho Chi Minh City, 2004–2008

Abstract: BackgroundThe dominant viral etiologies responsible for acute respiratory infections (ARIs) are poorly understood, particularly among hospitalized children in resource-limited tropical countries where morbidity and mortality caused by ARIs are highest. Improved etiological insight is needed to improve clinical management and prevention.ObjectivesWe conducted a three-year prospective descriptive study of severe respiratory illness among children from 2 months to 13 years of age within the largest referral hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

36
106
6
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(156 citation statements)
references
References 33 publications
36
106
6
5
Order By: Relevance
“…The detection rate for RSV was highest in winter, consistent with findings reported in Nanjing and Jinan, China (8,11). However, a report from Vietnam showed that RSV was prevalent in summer (13). Wet weather and cold weather are risk factors for RSV infection.…”
Section: Discussionsupporting
confidence: 85%
“…The detection rate for RSV was highest in winter, consistent with findings reported in Nanjing and Jinan, China (8,11). However, a report from Vietnam showed that RSV was prevalent in summer (13). Wet weather and cold weather are risk factors for RSV infection.…”
Section: Discussionsupporting
confidence: 85%
“…The high season for HMPV in tropical and subtropical areas varies-winter to spring in Brazil (27), spring and/or summer in Taiwan (28,29), and the rainy season in Vietnam (30). In this study, HMPV did not appear to have a high season in Okinawa.…”
contrasting
confidence: 53%
“…Respiratory viral infection, particularly infection of influenza and rhinoviruses, were associated with high rates of SARI hospitalization, and future studies correlating the clinical aspects are needed to design interventions, including targeted vaccination. the cause of an outbreak (3)(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%